2012
DOI: 10.1160/th11-12-0827
|View full text |Cite
|
Sign up to set email alerts
|

The HAS-BLED score predicts bleedings during bridging of chronic oral anticoagulation

Abstract: Patients who receive long-term oral anticoagulant (OAC) therapy often require interruption of OAC for an elective invasive procedure. Current guidelines allow bridging therapy with either unfractionated heparin (UFH) or low-molecular-weight heparin (LMWH). Apart from the risk of embolism, bleeding is an important complication in this setting and the optimal perioperative management of such patients is still under discussion. The aims of this prospective, observational, multicentre registry of patients treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Thus far, the HAS‐BLED score has been validated in several cohorts and is able to predict major bleeding in various clinical settings 31, 32, 33, 34. Several studies reported about the comparison between HAS‐BLED and other bleeding risk scores in vitamin K antagonist‐treated cohorts 31, 35, 36, 37, 38, 39.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the HAS‐BLED score has been validated in several cohorts and is able to predict major bleeding in various clinical settings 31, 32, 33, 34. Several studies reported about the comparison between HAS‐BLED and other bleeding risk scores in vitamin K antagonist‐treated cohorts 31, 35, 36, 37, 38, 39.…”
Section: Discussionmentioning
confidence: 99%
“…Regimens with a dose intermediate in anticoagulant intensity between high- and low-dose regimens (half-therapeutic dose) are commonly used for perioperative bridging of non-cancer patients, and many physicians have personal experience with half-therapeutic dosing [36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…For clopidogrel, maximum platelet function inhibition is achieved within 5 to 10 days when starting with a 75 -mg maintenance dose as opposed to 12-to 15 -hour maximal antiplatelet effect when clopidogrel is started with a 300-to 600 -mg loading dose; consequently, postoperative resumption of found that a score of 3 or higher was associated with a 12 -fold increased risk for clinically relevant bleeding, although the overall risk was only 3.5%. 27 However, this score was applied to patients who were receiving anticoagulant therapy, although it is likely that some of Eye procedures Phacoemulsification (cataract) P = 0.02), but it was underpowered to detect differences in bleeding outcomes. The most compelling findings are derived from the POISE -2 trial.…”
mentioning
confidence: 99%